(untitled) (Anclajes, 2020)
A problematic link made of tensions and contradictions relates Elvira Orphée to Tucumán, the Argentinian province where she was born and the space represented in many of her texts. This paper explores one of the aspects of this problematic link by revealing the fact that the author’s figure is fictionalized in Pretérito perfecto, novel published in 1983 by another writer from Tucumán, Hugo Foguet. After pointing out the elements which allow to relate Negra Fortabat, the character in the novel, to Orphée, the analysis meditates on the probable reasons for such fictionalization and on its implications regarding the image that Foguet constructs of himself as a writer. It is postulated that the figurative presence of Orphée in Pretérito perfecto works in at least three directions, intimately related to each other: 1) to develop the dispute over how to write a novel in general and how to write a novel about Tucumán in particular; 2) to incarnate the counter figure of a writer, which enables to make a necessary tabula rasa over every antecedent and to show, in that way, how disruptive and foundational the novel by Foguet is in itself; 3) to represent the tensions between a peripheral literary field located in Tucumán and a central literary field located in Buenos Aires.